Mass customization: Implementing the emerging paradigm for competitive advantage - Kotha, Suresh (Strategic Management Journal, 1995)
In many industries the dominant paradigm, ‘mass production,’ is being challenged by the emerging paradigm, ‘mass customization.’ Accordingly, many researchers posit that firms which replace ‘mass production’ with ‘mass customization’ will gain a significant competitive advantage. Based on an in-depth study of the National Bicycle Industrial Company (NBIC), this paper explores the dynamics of pursuing both mass production and mass customization strategies simultaneously. At the operational level, the paper discusses the organizational mechanisms instituted by the NBIC in order to benefit from the simultaneous pursuit of both approaches. At the competitive level, it isolates the relative contributions of both approaches to the overall competitive positioning of this firm in its industry. Based on this discussion, it provides a framework that illustrates the dynamics involved in the pursuit of both approaches. Implicitly, the paper argues that for firms competing in rapidly changing environments the ability to maintain a sustainable competitive advantage depends on the firm's capability to create knowledge by interacting both mass customization and mass production approaches. Finally, the paper concludes with managerial and research implications regarding the emerging paradigm of mass customization.